2006
DOI: 10.1097/00008877-200609000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary chelators as antioxidant enzyme mimetics: implications for dietary intervention in neurodegenerative diseases

Abstract: Following recent reviews on the role of metal ions in oxidative stress and neurodegenerative diseases, this article reports advances in the study of dietary components for the control of these conditions. Poor metal ion homeostasis is credited with pathological roles in the progression of a number of disorders including Alzheimer's disease, Parkinson's disease and multiple sclerosis. Synthetic metal ion chelators continue to show promise as a new therapeutic approach for neurodegenerative disorders. Dietary ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…893 Other researchers have confirmed these results and identified possible pathways of inhibition, 894 while some suggest that APP expression is reduced via iron chelation. 467 Curcumin is found in the Indian spices turmeric and curry and is known to be an antioxidant metal chelator 895 that binds to a large range of biological targets, as recently reviewed. 896 Epidemological studies have found that the incidence of AD among people in their 70s was about 4−5 times smaller in India than in the US and that curry consumption correlated with this tendency.…”
Section: Natural Metal Chelators Againstmentioning
confidence: 99%
“…893 Other researchers have confirmed these results and identified possible pathways of inhibition, 894 while some suggest that APP expression is reduced via iron chelation. 467 Curcumin is found in the Indian spices turmeric and curry and is known to be an antioxidant metal chelator 895 that binds to a large range of biological targets, as recently reviewed. 896 Epidemological studies have found that the incidence of AD among people in their 70s was about 4−5 times smaller in India than in the US and that curry consumption correlated with this tendency.…”
Section: Natural Metal Chelators Againstmentioning
confidence: 99%
“…Other molecules that are not themselves directly antioxidant, but have iron-binding characteristics, may also be of benefit. This is certainly true of phytic acid (phytate; myo-inositol-1,2,3,4,5,6-hexakis phosphate; CHEBI 17401) (Aljandali et al 2001; Allen and Cornforth 2009; Brune et al 1989; Davidsson et al 1994; Doria et al 2009; Glahn et al 2002; Graf and Eaton 1990, 1993; Graf et al 1987; Grases et al 2001; Hallberg et al 1989; Han et al. 1994; Hanson et al 2006; Hawkins et al 1993; Kamp et al 1995a, b, 2002; Kim et al 2008; Kumar et al 2010; Minihane and Rimbach 2002; Miyamoto et al 2000; Panduri et al 2006; Poser et al 2004; Rao et al 1991; Rimbach et al 2008; Sandberg et al 1999; Schlemmer et al 2009; Shamsuddin 1995; Vucenik and Shamsuddin 2006; Xu et al 2008).…”
Section: Catalytic Behaviour Of Polypeptides and Proteinsmentioning
confidence: 99%
“…Green tea has a high content of catechins [70] (a subclass of polyphenols), with epigallocatechin gallate ( EGCG ) (Fig. 3A) estimated to account for two-thirds of catechin content [71]. As antioxidants, an in vitro study found, tea catechins could inhibit the activities of cytochrome p450 2E1, Glutathione-S-Transferase, as well as lipid peroxidation [72].…”
Section: Plant Polyphenols As Multifunctional Neuroprotective Agentsmentioning
confidence: 99%